Potential diagnostic value of N1LR and SNHG1 in acute myocardial infarction - Wei Zhu; Li Luo; Guangning Ye; Jiaman Ou (BMC, 2023)
Abstract Introduction Acute myocardial infarction (AMI) is a common cardiovascular disease that can lead to myocardial necrosis and a poor prognosis. Clinical practice requires an accurate and quick diagnosis of AMI due to the inherent limitations of current biomarkers. Therefore, research into novel biomarkers is necessary. We aimed to explore the diagnostic potency of the long non-coding RNA (lncRNA) N1LR and SNHG1 in patients diagnosed with AMI. Method We measured lncRNA levels in 148 AMI patients and 50 healthy volunteers with quantitative RT-PCR method. Receiver operating characteristic (ROC) analysis was administered to detect the diagnostic power of selected lncRNAs. Correlation analysis was performed to explore the relationship between N1LR as well as SNHG1 and the conventional myocardial biomarkers (LDH, CK, CKMB and cTnI). Results ROC analysis reveals the possibility of N1LR and SNHG1 as biomarkers in AMI diagnosis (AUC of N1LR: 0.873; AUC of SNHG1: 0.890). Correlation analysis revealed that N1LR was negatively correlated with the conventional biomarkers and SNHG1 was positively correlated with the conventional biomarkers. Conclusion For the first time, we investigated the potential predictive diagnostic value of N1LR and SNHG1 in AMI diagnosis and substantial outcomes were obtained. Also, they may be capable of reflecting the progress of the disease during clinical practice from the correlation analysis.